The Birth of I-Kelahiran – Sabah’s experience - Dhesi Baha, Raja Selva Raja; Cheah, W.L (University of Illinois at Chicago, 2014)
Though over the years, Sabah has recorded an increase of childbirth with better healthcare indicators, improving maternal and childcare has always been a major challenge. Therefore, with the aim of addressing the current issues of birthing discrepancy, delayed reporting of high risk pregnancy and maximum immunization coverage within the state of Sabah, “I-Kelahiran”: Inovasi Kelahiran: was developed in June 2012. This computerised birthing system acts not only as an online storehouse of information, it also traces data and generates reports to reduce enormous duplication, save cost and time, as well as eliminating delays and confusion on management of health information. The system also helps to overcome the issue of collecting data from rural health personnel, particularly with the extreme geographical terrain in Sabah. This paper discusses how I-Kelahiran, a health information system was developed under the Sabah Health Department and shares its experiences in implementation. The experience and feedback from this system will help to build a full-fledged system capable of handling childbirth data at the higher level in Borneo.